Genotype directed therapy in murine mismatch repair deficient tumors. - Melanie H Kucherlapati; Shadi Esfahani; Peiman Habibollahi; Junning Wang; Eric R Still; Roderick T Bronson; Umar Mahmood; Raju S Kucherlapati (PLoS ONE, 2013)
The PI3K/AKT/mTOR pathway has frequently been found activated in human tumors. We show that in addition to Wnt signaling dysfunction, the PI3K/AKT/mTOR pathway is often upregulated in mouse Msh2(-/-) initiated intestinal tumors. NVP-BEZ235 is a dual PI3K/mTOR inhibitor toxic to many cancer cell lines and currently involved in clinical trials. We have treated two mouse models involving Msh2 that develop small intestinal and/or colonic tumors with NVP-BEZ235, and a subset of animals with NVP-BEZ235 and MEK inhibitor ADZ4266. The disease phenotype has been followed with pathology, (18)F FDG PET imaging, and endoscopy. Intestinal adenocarcinomas are significantly decreased in multiplicity by both drug regimens. The majority of tumors treated with combined therapy regress significantly, while a small number of highly progressed tumors persist. We have examined PTEN, AKT, MEK 1&2, MAPK, S6K, mTOR, PDPK1, and Cyclin D1 and find variable alterations that include downregulation of PTEN, upregulation of AKT and changes in its phosphorylated forms, upregulation of pMEK 1&2, p42p44MAPK, pS6K, and Cyclin D1. Apoptosis has been found intact in some tumors and not in others. Our data indicate that NVP-BEZ235 alone and in combination with ADZ4266 are effective in treating a proportion of colorectal cancers, but that highly progressed resistant tumors grow in the presence of the drugs. Pathways upregulated in some resistant tumors also include PDPK1, suggesting that metabolic inhibitors may also be useful in treating these tumors.